Comparison of chest radiography, chest tomosynthesis and computed tomography for detection of pulmonary nodules: A phantom study: Comparison between CXR, CDT and CT - T, Kattipathanapong; J, Euathrongchit; Y, Wannasopha; S, Ua-Apisitwong; K, Jirapong; S, Saeteng; A, Tantraworasin; N, Lertprasertsuke (Biomedical Sciences and Clinical Medicine, 2019)
Objective To compare the rate of pulmonary nodule detection using chest radiograph, chest digital tomosynthesis and computed tomography examination. Methods After institutional review broad approval, an in-house chest phantom was made from acrylic, plaster and catheters. Plastic beads of 1-2 mm, 3-4 mm, 5-6 mm, 7-8 mm and 9-10 mm were implanted in the phantom to represent pulmonary nodules. From 0 to 20 nodules were randomly embedded in each model and the model was photographed by digital chest radiograph (CXR), chest digital tomosynthesis (CDT) and chest computed tomography (CT). Two blinded thoracic radiologists reviewed and marked the nodules on each of 34 images. The percentage of nodules detected with each method was calculated and compared. Results There were a total of 332 nodules in the 34 phantom models. Overall nodule detection rates were 75.3% for CXR, 91.0% for CDT and 98.8% for CT. With CT, all nodules larger than 3 mm in diameter were identified. With CDT, over 90% of the nodules larger than 5 mm were detected. The percentage detected with CDT and CT was not statistically significantly different for 5-10 mm nodules. The regions of poorest nodular detection with CXR were the mediastinum and hilum regions, while with CDT it was the costophrenic sulcus. Conclusion CT provides the highest percentage of nodular detection, followed by CDT and digital CXR in that order. There is no significant difference in percentage detection between CT and CDT for 5-10 mm nodules.